What kind of Agencification in Croatia? Trends and Future Directions - Anamarija MUSA; Ivan KOPRIĆ (Transylvanian Review of Administrative Sciences, 2011)
The paper presents the current state of the process of agencification in Croatia, pointing out both the process and the institutional design. The agency model in Croatia consists of several types of more or less autonomous administrative organizations, situated at different distances from the central government. The most evident pressures for agencification come from decentralization, managerial responses and Europeanization. The reversal of the process in recent years has mostly happened because of the need for rationalization of the public administration system, which is also under pressure because of the economic crisis. The key problems of the agency model are over politicization on the one hand, and insufficient and inadequate control on the other. The adequate legal framework for agencies would enhance institutionalization of the agency model, ensuring effectiveness and legal certainty and maintaining a sufficient level of independence.